Proceedings of the 12th Asia Pacific Physics Conference (APPC12) 2014
DOI: 10.7566/jpscp.1.015044
|View full text |Cite
|
Sign up to set email alerts
|

Electron and Ion Heating During Magnetic Reconnection in Weakly Collisional Plasmas

Abstract: Gyrokinetic simulations of magnetic reconnection are presented to investigate plasma heating for strongly magnetized, weakly collisional plasmas. For a low plasma beta case, parallel and perpendicular phase mixing strongly enhance energy dissipation yielding electron heating. Heating occurs for a long time period after a dynamical process of magnetic reconnection ended. For a higher beta case, the ratio of ion to electron dissipation rate increases, suggesting that ion heating (via phase-mixing) may become an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
4
11
0
Order By: Relevance
“…It is important to point out that the restriction to low β e limits the applicability of our conclusions in the solar wind, where, more often than not, β e ∼ 1, but our results will be more relevant to the turbulence closer to the Sun and in the corona: indeed, at the perihelion (approximately 10 solar radii) of the upcoming Parker Solar Probe mission, β e ≈ 0.01, at least in fast-solar-wind streams (Chandran et al 2011). Moreover, the growth-rate scaling (3.2) appears to be quite robust even at moderately large β e : Numata & Loureiro (2015) showed that, keeping all other parameters fixed, γ > ∝ β −1/2 e ∝ d e up to at least β e = 10, in agreement with (3.2), and despite the width of the reconnecting layer being set by ρ e rather than d e . Therefore, we expect our conclusions to be at least qualitatively relevant at β e ∼ 1.…”
Section: Collisionless Tearing Modementioning
confidence: 56%
“…It is important to point out that the restriction to low β e limits the applicability of our conclusions in the solar wind, where, more often than not, β e ∼ 1, but our results will be more relevant to the turbulence closer to the Sun and in the corona: indeed, at the perihelion (approximately 10 solar radii) of the upcoming Parker Solar Probe mission, β e ≈ 0.01, at least in fast-solar-wind streams (Chandran et al 2011). Moreover, the growth-rate scaling (3.2) appears to be quite robust even at moderately large β e : Numata & Loureiro (2015) showed that, keeping all other parameters fixed, γ > ∝ β −1/2 e ∝ d e up to at least β e = 10, in agreement with (3.2), and despite the width of the reconnecting layer being set by ρ e rather than d e . Therefore, we expect our conclusions to be at least qualitatively relevant at β e ∼ 1.…”
Section: Collisionless Tearing Modementioning
confidence: 56%
“…Observationally, there have been attempts to measure the kinetic entropy or use entropic measures with satellite observations of, for example, Earth's magnetotail plasma sheet (Kaufmann & Paterson 2009, 2011), Earth's bow shock (Parks et al 2012), the near-Earth solar wind (Weck et al 2015;Olivier, Engelbrecht & Strauss 2019) and auroral currents (Osmane, Dimmock & Pulkkinen 2019). It has also been used in a number of theoretical and numerical studies (Montgomery & Nielson 1970;Hsu, Joyce & Montgomery 1974;Krommes & Hu 1994;Leubner 2004;Watanabe & Sugama 2004;Howes et al 2006;Sarazin et al 2009;Tatsuno et al 2009;Nariyuki 2011;Nakata, Watanabe & Sugama 2012;Loureiro, Schekochihin & Zocco 2013;TenBarge & Howes 2013;Numata & Loureiro 2015;Pezzi, Valentini & Veltri 2016;Grošelj et al 2017;Hesse et al 2017;Pezzi 2017;Cerri, Kunz & Califano 2018;Eyink 2018;Gary et al 2018;Kawazura, Barnes & Schekochihin 2019;Liang et al 2019;Pezzi et al 2019;Du et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we also found smaller reconnection rates in the high beta case compared to the low beta one, in agreement with previous studies of gyrokinetic simulations of magnetic reconnection. 39,40 However, we can notice in Fig. 1 that the reconnection values for both low and high plasma β cases are still a substantial fraction of (dΨ/dt)/Ψ N ∼ 0.1.…”
Section: A Global Evolutionmentioning
confidence: 90%